ESENSI PEMAKZULAN PRESIDEN DALAM SISTEM PEMERINTAHAN PRESIDENSIAL - A. Sakti R.S. Rakia; Imam Satria Aradina (Media Keadilan: Jurnal Ilmu Hukum, 2022)
One of the essences of implementing state government with a presidential system of government is the process of direct accountability to the people. This means that the people must be involved in every administration of government, including the process of impeaching the president. In Indonesia, the process of impeachment against the President is predominantly carried out by the Parliament, which is actually a practice in a parliamentary system of government. This study aims to analyze the essence of presidential impeachment in the presidential government system in Indonesia. The method used in this study is normative juridical research with a statute approach, which is carried out in a descriptive-analytical manner. The results of this study indicate that the impeachment process of the President of Indonesia is not purely an impeachment process that is in accordance with the presidential government system. In addition, the process of impeaching the President does not involve the people as the holders of sovereignty because there are no constitutional provisions that regulate it.Keywords: impeachment; presidential system; constitutional law. ABSTRAKSalah satu hakikat dari pelaksanaan pemerintahan negara dengan sistem pemerintahan presidensial adalah proses pertanggungjawaban langsung kepada rakyat. Artinya, rakyat mesti terlibat dalam setiap penyelenggaraan pemerintahan, termasuk mengenai proses pemakzulan presiden. Di Indonesia, proses pemakzulan terhadap Presiden dominan dilakukan oleh Parlemen yang sebenarnya praktik seperti ini adalah praktik dalam sistem pemerintahan parlementer. Penelitian ini bertujuan untuk menganalisis esensi pemakzulan presiden dalam sistem pemerintahan presidensial di Indonesia. Metode yang digunakan dalam penelitian ini adalah penelitian yuridis normatif dengan pendekatan statuta approach yang dilakukan secara deskriptis-analitis. Hasil penelitian ini menunjukan bahwa proses pemakzulan Presiden di Indonesia tidak murni merupakan proses pemakzulan yang sesuai dengan sistem pemerintahan presidensial. Selain itu, proses pemakzulan Presiden tidak melibatkan rakyat sebagai pemegang kedaulatan, karena tidak ada ketentuan konstitusi yang mengaturnya.Kata Kunci: Pemakzulan Presiden; Sistem Presidensial; Hukum Konstitusi.